INCLUSIVE EDUCATION AND HIGHER EDUCATION FROM THE VIEWPOINT OF STUDENTS WITH FUNCTIONAL DIVERSITY - Moriña, Anabel (2017)
This article presents the results of a research that sought to analyze the facilitators and obstacles that three students with functional diversity identified during their career in the university, namely how teachers had been able to contribute to their social and educational inclusion. From the biographical-narrative method was intended to give voice to people with functional diversity. For the collection of information, a variety of qualitative instruments were used: biographical interviews, focused interviews, semistructured interviews, photographs, self reports, lifeline, researcher’s field diary, Emails and the technique “A day in the life of ...” A narrative analysis was carried out that allowed to construct three histories of life. In particular, the results of this work, through the narratives of Marper, Andrés and Rafa, focus on analyzing how teachers contributed or not to the inclusion of students and what were the main barriers that identify referred to it. Among the main conclusions, it should be pointed out that some teachers were not sufficiently trained to respond to the needs of the students or because, sometimes, the necessary adjustments were not made for student learning and participation.